Legal Protection For Victims Of Online Auction Group As A Result Of The Difficulty Of Getting New Members, As Seen From A Civil Law Perspective - Kusmiati, N. Ike; Raynaldo, Randy (Dinasti Research, 2025)
Arisan (a social gathering) is an activity where several people pool money or goods of equal value and then draw lots among the participants to determine who wins. Arisan is recognized as an agreement, although it is often based on mutual consent of the participants without formal written agreement. Arisan falls into the category of anonymous agreements. Therefore, when conducting an arisan, the requirements stipulated in Article 1320 of the Civil Code must be considered. The method used in this research is descriptive and analytical, addressing the research problem, specifically the legal protection of victims of online auction arisan due to the difficulty of attracting new members from a civil law perspective. The results indicate that the implementation of online auction arisan, which relies on recruiting new members, poses significant legal risks, particularly due to the weak basis of the agreement, which is often verbal and lacks written evidence. Protection for victims of online auction arisan (raising) can be provided, despite the lack of explicit regulations, through general principles of agreements, provisions of the Civil Code, the Electronic Information and Transactions Law (UU ITE), and OJK regulations. Legal actions that victims can take include non-litigation resolutions such as mediation and negotiation, as well as litigation through lawsuit mechanisms.